A genetic IFN/STAT1/FAS axis determines CD4 T stem cell memory levels and apoptosis in healthy controls and Adult T-cell Leukemia patients. (4th May 2018) - Khouri, Ricardo; Silva-Santos, Gilvanéia; Dierckx, Tim; Menezes, Soraya Maria; Decanine, Daniele; Theys, Kristof; Silva, Aline Clara; Farré, Lourdes; Bittencourt, Achiléa; Mangino, Massimo; Roederer, Mario; Vandamme, Anne-Mieke; et al.
ABSTRACT: Adult T-cell leukemia (ATL) is an aggressive, chemotherapy-resistant CD4 + CD25 + leukemia caused by HTLV-1 infection, which usually develops in a minority of patients several decades after infection. IFN + AZT combination therapy has shown clinical benefit in ATL, although its mechanism of action remains unclear. We have previously shown that an IFN-responsive FAS promoter polymorphism in a STAT1 binding site (rs1800682) is associated to ATL susceptibility and survival. Recently, CD4 T stem cell memory (TSCM ) Fas hi cells have been identified as the hierarchical cellular apex of ATL, but a possible link between FAS, apoptosis, proliferation and IFN response in ATL has not been studied. In this study, we found significant ex vivo antiproliferative, antiviral and immunomodulatory effects of IFN-α treatment in short-term culture of primary mononuclear cells from ATL patients (n = 25). Bayesian Network analysis allowed us to integrate ex vivo IFN-α response with clinical, genetic and immunological data from ATL patients, thereby revealing a central role for FAS -670 polymorphism and apoptosis in the coordinated mechanism of action of IFN-α. FAS genotype-dependence of IFN-induced apoptosis was experimentally validated in an independent cohort of healthy controls (n = 20). The same FAS -670 polymorphism also determined CD4 TSCM levels in a genome-wide twin study (p = 7 × 10 −11, n = 460), confirming a genetic link between apoptosis and TSCM levels. Transcriptomic analysis and cell type deconvolution confirmed the FAS genotype/TSCM link and IFN-α-induced downregulation of CD4 TSCM -specific genes in ATL patient cells. In conclusion, ex vivo IFN-α treatment exerts a pleiotropic effect on primary ATL cells, with a genetic IFN/STAT1/Fas axis determining apoptosis vs. proliferation and underscoring the CD4 TSCM model of ATL leukemogenesis.